2002
DOI: 10.1002/14651858.cd002234
|View full text |Cite|
|
Sign up to set email alerts
|

Ribavirin with or without alpha interferon for chronic hepatitis C

Abstract: Combination therapy increased the number of naive patients, relapsers, and non-responders with a sustained virological, biochemical, or histological response, but also the occurrence of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 193 publications
0
4
0
Order By: Relevance
“…Twelve studies regarding the medical efficacy of combination therapy with interferon plus ribavirin compared to interferon monotherapy were included; herein 2 HTA reports [38], [39] 1 systematic Cochrane review [24], 2 meta-analyses [23], [40] and 7 controlled randomised clinical trials [41], [42], [43], [44], [13], [14], [45]. Two controlled randomised multicentre studies [15], [16] regarding medical efficacy of combination therapy with peginterferon and ribavirin compared to interferon plus ribavirin were identified and included.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve studies regarding the medical efficacy of combination therapy with interferon plus ribavirin compared to interferon monotherapy were included; herein 2 HTA reports [38], [39] 1 systematic Cochrane review [24], 2 meta-analyses [23], [40] and 7 controlled randomised clinical trials [41], [42], [43], [44], [13], [14], [45]. Two controlled randomised multicentre studies [15], [16] regarding medical efficacy of combination therapy with peginterferon and ribavirin compared to interferon plus ribavirin were identified and included.…”
Section: Resultsmentioning
confidence: 99%
“…Several randomised trials [41], [42], [43], [44], [13], [14], [45] and meta-analyses [23], [24], [40] reported combination therapy with interferon plus ribavirin to be more efficient than interferon monotherapy (SVR: 32-54% vs. 8-21%). Two randomised multicentre studies [15], [16] reported a higher SVR for peginterferon plus ribavirin compared to combination therapy with interferon plus ribavirin (54-56% vs. 44-47%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations